2020
DOI: 10.1177/0271678x20953913
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal monitoring of microglial/macrophage activation in ischemic rat brain using Iba-1-specific nanoparticle-enhanced magnetic resonance imaging

Abstract: Microglial/macrophage activation plays a dual role in response to brain injury after a stroke, promoting early neuroinflammation and benefit for neurovascular recovery. Therefore, the dynamics of stroke-induced cerebral microglial/macrophage activation are of substantial interest. This study used novel anti-Iba-1-targeted superparamagnetic iron–platinum (FePt) nanoparticles in conjunction with magnetic resonance imaging (MRI) to measure the spatiotemporal changes of the microglial/macrophage activation in livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…This has indeed been demonstrated for microglia or macrophages using Iba-1 (ionized calcium binding adaptor molecule 1) antibody-conjugated superparamagnetic nanoparticles, measured in rats up to 4 weeks after transient MCAO. 115 Conversely, iron oxide particles may be coated with a natural leukocyte membrane to target activated endothelium, demonstrated using neutrophilmimetic magnetic nanoprobes in poststroke mice. 116 Another approach for in vivo imaging of neuroinflammation involves using responsive contrast agents.…”
Section: Imaging Molecular Markers Of Inflammationmentioning
confidence: 99%
“…This has indeed been demonstrated for microglia or macrophages using Iba-1 (ionized calcium binding adaptor molecule 1) antibody-conjugated superparamagnetic nanoparticles, measured in rats up to 4 weeks after transient MCAO. 115 Conversely, iron oxide particles may be coated with a natural leukocyte membrane to target activated endothelium, demonstrated using neutrophilmimetic magnetic nanoprobes in poststroke mice. 116 Another approach for in vivo imaging of neuroinflammation involves using responsive contrast agents.…”
Section: Imaging Molecular Markers Of Inflammationmentioning
confidence: 99%
“…Superparamagnetic iron–platinum nanoparticles targeted with novel anti-Iba-1 together with MRI studied in a four-week post-stroke surviving rat brain were used to measure the spatio temporal changeson the microglial/macrophage. The data revealed that nanoparticle-enhanced MRI scans could be an effective monitoring method to understand the neuroinflammation development in live animals during the treatment of stroke as well as disease progression [ 153 ].…”
Section: Nanomaterials and Their Clinical Applicationmentioning
confidence: 99%
“…With the help of nanoparticles, MRI enables accurate monitoring of neuroinflammatory progression. Sillerud et al ( 2020 ) used novel anti-Iba-1-targeted superparamagnetic iron-platinum (FePt) nanoparticles in conjunction with T2-weighted magnetic resonance imaging (MRI) to measure the spatiotemporal changes of the microglial/macrophage activation in the living rat brain for 4 weeks post-stroke. They found that this approach could monitor the dynamic development of active neuroinflammation during stroke progression and treatment (Sillerud et al, 2020 ).…”
Section: Nanomaterials-based Diagnosismentioning
confidence: 99%
“…Sillerud et al ( 2020 ) used novel anti-Iba-1-targeted superparamagnetic iron-platinum (FePt) nanoparticles in conjunction with T2-weighted magnetic resonance imaging (MRI) to measure the spatiotemporal changes of the microglial/macrophage activation in the living rat brain for 4 weeks post-stroke. They found that this approach could monitor the dynamic development of active neuroinflammation during stroke progression and treatment (Sillerud et al, 2020 ). Jin et al ( 2016 ) show that magnetic resonance imaging (MRI) or Xenogen imaging combined with the labeling of SPIO-Molday ION Rhodamine-B (MIRB) can be used to monitor the dynamics of CD4(+) T cells in the ischemic area after stroke.…”
Section: Nanomaterials-based Diagnosismentioning
confidence: 99%